How to change : the science of getting from where you are to where you want to be - Milkman, Katherine L. (Portfolio/Penguin, an imprint of Penguin Random House LLC, 2021)
"Award-winning Wharton Professor and Choiceology podcast host Katy Milkman has devoted her career to the study of behavior change. In this ground-breaking book, Milkman reveals a proven path that can take you from where you are to where you want to be, with a foreword from psychologist Angela Duckworth, the best-selling author of Grit. Set audacious goals. Foster good habits. Create social support. You've surely heard this advice before. If you've ever tried to change or encourage it -- to boost exercise or healthy eating, to prevent missed deadlines or kick-start savings -- then you know there are thousands of apps, books, and YouTube videos promising to help and offering sound guidance. And yet, you're still not where you want to be. This trailblazing book from award-winning behavioral scientist and Wharton Professor Katy Milkman explains why. In a career devoted to uncovering what helps people change, Milkman has discovered a crucial thing many of us get wrong: our strategy. Change, she's learned, comes most readily when you understand what's standing between you and success and tailor your solution to that roadblock. If you want to work out more but find exercise difficult and boring, downloading a goal-setting app probably won't help. But what if, instead, you transformed your workouts so they became a source of pleasure instead of a chore? Turning an uphill battle into a downhill one is the key to success. Drawing on Milkman's original research and the work of her dozens of world-renowned scientific collaborators, How to Change shares an innovative new approach that will help you change or encourage change in others. Through case studies, engaging stories, and examples from cutting-edge research, this book illustrates how to identify and overcome the barriers that regularly stand in the way of change. How to Change will teach you: Why timing can be everything when it comes to making a change How to turn temptation and inertia into assets that can help you conquer your goals That giving advice, even if it's about something you're struggling with, can help you achieve more Whether you're a manager, coach, or teacher aiming to help others change for the better or are struggling to kick-start change yourself, How to Change offers an invaluable, science-based blueprint for achieving your goals, once and for all"--